JAK2-V617F and interferon-α induce megakaryocyte-biased stem cells characterized by decreased long-term functionality - Rao, Tata Nageswara; Hansen, Nils; Stetka, Jan; Luque Paz, Damien; Kalmer, Milena; Hilfiker, Julian; Endele, Max; Ahmed, Nouraiz; Kubovcakova, Lucia; Rybarikova, Margareta; Hao-Shen, Hui; Geier, Florian; et al. (Blood, 2021)
We studied a subset of hematopoietic stem cells (HSCs) that are defined by elevated expression of CD41 (CD41hi) and showed bias for differentiation toward megakaryocytes (Mks). Mouse models of myeloproliferative neoplasms (MPNs) expressing JAK2-V617F (VF) displayed increased frequencies and percentages of the CD41hi vs CD41lo HSCs compared with wild-type controls. An increase in CD41hi HSCs that correlated with JAK2-V617F mutant allele burden was also found in bone marrow from patients with MPN. CD41hi HSCs produced a higher number of Mk-colonies of HSCs in single-cell cultures in vitro, but showed reduced long-term reconstitution potential compared with CD41lo HSCs in competitive transplantations in vivo. RNA expression profiling showed an upregulated cell cycle, Myc, and oxidative phosphorylation gene signatures in CD41hi HSCs, whereas CD41lo HSCs showed higher gene expression of interferon and the JAK/STAT and TNFα/NFκB signaling pathways. Higher cell cycle activity and elevated levels of reactive oxygen species were confirmed in CD41hi HSCs by flow cytometry. Expression of Epcr, a marker for quiescent HSCs inversely correlated with expression of CD41 in mice, but did not show such reciprocal expression pattern in patients with MPN. Treatment with interferon-α further increased the frequency and percentage of CD41hi HSCs and reduced the number of JAK2-V617F+ HSCs in mice and patients with MPN. The shift toward the CD41hi subset of HSCs by interferon-α provides a possible mechanism of how interferon-α preferentially targets the JAK2 mutant clone.
Keywords: bodová mutace; Janus Kinase 2; myši; lidé; Humans; Myeloproliferative Disorders; Mice; Animals; interferon alfa; Gene Knock-In Techniques; genový knockin; Interferon-alpha; Megakaryocytes; hematopoetické kmenové buňky; zvířata; Hematopoietic Stem Cells; trombocytový membránový glykoprotein IIb; megakaryocyty; Point Mutation; myši transgenní; Platelet Membrane Glycoprotein IIb; Janus kinasa 2; myeloproliferativní poruchy; Mice, Transgenic